Induction of Colicin la at High Temperature - Gromkova, Rosa H. (1971)
Induction of colicin la at a high temperature (42 C) was demonstrated in a wild strain of Shigella sonnei. After transfer of the Col factor, a similar effect was observed in those recipient cells acquiring colicinogeny. The induction is suggested to be due to the presence of a thermosensitive colicin repressor. The wild-type strain segregated sensitive cells and showed heterogeneity in colicin production.